Research on the concept “restoration” of the testorative justice (Journal of actual problems of jurisprudence, 2022)
Restorative justice, which originated in the 1970s, has been applied to various crime response systems worldwide. The judicial practice of foreign countries has proved that the restorative judicial system has the benign value of complementing the traditional criminal justice system, which has the disadvantages of diluting the interests of victims and the stability of the community, failing to prevent crimes, and not conducive to helping the offender to return to society. Restoration is the precondition of restorative justice, so implantation of restorative justice must correctly understand the leading concept of restoration. This paper conducts inspections on “restoration” from three dimensions. First, in the existential dimension, this paper did research on the etymological interpretation of “restoration of restorative judicial” and its meaning in historical evolution, and proposed that the concept of “restoration” must include efficiency and economic content; secondly, in the normative dimension, this paper explained the two-dimensional structure of the internal time dimension and participation dimension of the concept of “restoration”; finally, in the value dimension, this paper deconstructed the internal oppositional elements of the concept of “restoration”, and pointed out the trend of elimination of barriers among the elements inside the concept of “restoration”.Keywords: restoration; two-dimensional structure; various elements; deconstruction